Mental health and catastrophic health expenditures in conflict-affected regions of Colombia before and during COVID-19: an inequalities perspective - Sebastian Leon-Giraldo; Nicolas Jater-Maldonado; Javier Garcia-Estevez; Oscar Bernal (International Journal for Equity in Health)
Abstract The objective of this study is to analyze the changes in catastrophic health expenditures (CHE) and out-of-pocket expenditures (OOP) before and during the COVID-19 pandemic, as well as to examine their determinants in Meta, Colombia, a region affected by armed conflict. We used data from the Conflicto, Paz y Salud (CONPAS) survey and applied mixed-effects logistic regression models. The analysis places particular emphasis on mental health as a key determinant, comparing the odds of incurring OOP and CHE between individuals with and without a tendency to present mental health disorders (SRQ + versus SRQ-). The results show that the odds of incurring CHE increased in 2020 compared to 2018, while the odds of incurring OOP decreased during the same period. Individuals living in less wealthy households (quintiles 1, 2, and 3 of the Household Wealth Index) have more odds of incurring CHE than those in the wealthiest group (quintile 5). Similarly, individuals aged 45 to 60 years or over 60 years and have more odds of incurring CHE than younger individuals (18 to 44 years). Those who fell sick or were hospitalized also have more odds of incurring CHE compared to those who did not. Additionally, we found that individuals with SRQ + have significantly higher odds of incurring OOP and marginally significantly higher odds of incurring CHE compared to SRQ- individuals. Additionally, those who have been displaced due to the conflict have higher odds of incurring OOP compared to those who have not. This study underscores the heightened vulnerability of regions impacted by violence; a situation further exacerbated by the COVID-19 pandemic. It emphasizes the need for targeted financial safeguards and comprehensive mental health programs to support marginalized communities, enhance economic resilience, and advance progress toward the Sustainable Development Goals (SDGs), particularly SDG 3, which aims to promote good health and well-being. The findings shed light on health disparities in violence-affected areas, highlighting the urgency of policies designed to improve financial security and healthcare access for individuals with mental health conditions.